PROTOTYPE ROBOT PENJINAK BOM TERINTEGRASI IP KAMERA DENGAN KOMUNIKASI WIRELESS BERBASIS MIKROKONTROLER ATMEGA 8535 - Medilla Kusriyanto; Alvin Sahroni; Damar Anggit (Faculty of Industrial Technology Universitas Islam Indonesia, 2015)
Bomb is an object with high destructive power. Today the bomb threat in Indonesia are common. Research earlier bomb squad robot has a weakness in the design of wireless communication and video viewer. This study tries to design a prototype robot bomb disposal by using IP cameras and wireless communication using a WIZnet based microcontroller interface ATMega8535. Video is displayed with MJPEG viewer designed using Visual Basic. The movement of the robot is set using the buttons on the monitoring software that is integrated with MJPEG viewer. From the test results obtained prototype robot can move in accordance with the existing arrangements on the monitoring system by using MJPEG as robot navigation. Robots also managed to pick up objects using a gripper simulated bomb and put it into a simulated bombing. In this study used camera is a camera that is found on android phone because of limited funds. The future can use the integrated camera with IP addressing